The Outlook for China's Growth and its Impact on New Zealand Exports - Scott Bowman; Patrick Conway (New Zealand Government, The Treasury, 2013)
The People's Republic of China has become increasingly important to the New Zealand economy since the start of economic liberalisation in China more than 30 years ago, particularly in the past decade. This paper is the second of three looking at the impact of China on the New Zealand economy. The first paper (Bowman and Conway, 2013) examined China's recent economic expansion and traced the channels through which this expansion has impacted on the New Zealand economy, concentrating on China's demand for commodities. This paper examines the sustainability of China's economic growth and demand for commodities, and the impact that China is likely to have on the New Zealand economy in the next decade. The third paper (Osborn and Vehbi, 2013) quantifies the impact of China's past expansion and commodity demand on the New Zealand economy through the framework of an econometric model. This paper concludes that while there are cyclical risks to China's economic performance in the medium term, these risks are manageable; China's economic growth is likely to ease to a more stable and sustainable rate over the next decade compared to the previous decade. However, demand for commodities is likely to remain high over this period, as urbanisation continues and incomes grow faster than other trading partners. A gradual shift in the driver of economic growth from investment to consumption is likely to transfer demand from hard to soft commodities. Dairy and meat consumption per capita are expected to grow as incomes increase and combined with China's large population will result in significant impacts on global markets. China's shortage of agricultural land and water resources will limit its supply response and, along with concerns about the quality of domestic production, result in a reliance on imports of agricultural products. New Zealand's reputation for producing quality products and its efficient supply chains, which are already well established, put it in a good position to benefit. China's growing share of New Zealand exports will continue to increase its contribution to New Zealand's economic growth, despite a slowdown in China's growth.
Keywords: F14; F43; 330; China; New Zealand; commodities; dairy; forestry; merchandise trade